One last promise - Warren, Susan May, 1966- (Alaska Air One Rescue, 2024)
"Waitress Tillie Young never thought her ex would track her to Alaska. When he kidnaps her daughter, she'll do anything to get her back-even enlist help from her favorite grumpy customer, pilot Arlo 'Moose' Mulligan. It will take all of Moose's Alaskan savvy to keep them alive-but who is going to protect him from the love he never saw coming?"--